The Mediating Role of Social Capital in Digital Information Technology Poverty Reduction an Empirical Study in Urban and Rural China - Zhen Liu; Yiming Wei; Qiuming Li; Jing Lan (Land, 2021)
Widespread use of digital information technology is having a significant impact on economic growth and people’s well-being. This paper assesses the mediating role of social capital in the impact of digital information technology on multidimensional poverty. Due to differences in regional, industrial structure and other factors, digital information technology has different impacts on urban and rural residents. In this paper, the China Family Panel Studies (CFPS) database is used for data, and a mediating effect model is used to study the problem. The digital information technology use was found to enhance social capital from social network, social participation and social trust, and subsequently alleviates multidimensional poverty. The results indicate that social trust plays a more significant mediating role than social capital and social participation on the impact of digital information technology on multidimensional poverty. Furthermore, the results reveal that the use of digital information technology has varying effects on poverty reduction among different income groups, with a much higher effect on low-income groups. However, the mediating effect of social capital in high-income groups is higher than that in low-income groups. In particular, social capital in the top 25% of income groups has the highest mediating effect. In the heterogeneity analysis between urban and rural areas, it is found that the multidimensional poverty situation in urban areas is significantly better than that in rural areas, because urban residents have a higher use of digital information, and at the same time, the quality of social capital in urban and rural groups is different, leading to the difference in the effect of digital information technology on poverty reduction of multidimensional poverty. Based on the results of the study, we believe that the use of digital information technology has actually improved the multi-dimensional poverty status of all groups, and social capital plays a key mediating role in it. Relying on the progress of digital information technology, we can build more convenient social network. Establish more adequate channels of information communication, enhance social trust and social participation, and alleviate multidimensional poverty.